2018
DOI: 10.1142/s0217751x18501890
|View full text |Cite
|
Sign up to set email alerts
|

Nutty black holes in Galileon scalar-tensor gravity

Abstract: Einstein gravity supplemented by a scalar field non-minimally coupled to a Gauss-Bonnet term provides an example of model of scalar-tensor gravity where hairy black holes do exist. We consider the classical equations within a metric endowed with a NUT-charge and obtain a two-parameter family of nutty-hairy black holes. The pattern of these solutions in the exterior and the interior of their horizon is studied in some details. The influence of both -the hairs and the NUT-charge -on the lightlike and timelike ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Nutty-Hairy black holes in Einstein-Chern-Simons gravity were constructed in [29] and [21] for γ 2 = 0 and γ 1 = 0 respectively. Similar solutions within Einstein-Gauss-Bonnet (rather than Chern-Simons) gravity were obtained in [23]. The field equations are given by (2.4) and (2.5) with a different expression of T (I) µν which can be found in [21] with the same notations as in Sect.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Nutty-Hairy black holes in Einstein-Chern-Simons gravity were constructed in [29] and [21] for γ 2 = 0 and γ 1 = 0 respectively. Similar solutions within Einstein-Gauss-Bonnet (rather than Chern-Simons) gravity were obtained in [23]. The field equations are given by (2.4) and (2.5) with a different expression of T (I) µν which can be found in [21] with the same notations as in Sect.…”
Section: Resultsmentioning
confidence: 69%
“…Solutions corresponding to the "-" sign can be constructed as well (see e.g. [23]), forming a second branch whith higher mass. This branch, however is difficult to construct numerically.…”
Section: Fundamental Branchmentioning
confidence: 99%
“…In these theories, it was shown that scalarized black holes exists for several choices of the non-minimal coupling function F (ψ) [30][31][32][33][34][35][36]. The first example was provided in [30,31] assuming a linear coupling (F (ψ) ∝ ψ).…”
Section: Introductionmentioning
confidence: 99%
“…In these theories, it was shown that scalarised black holes exists for several choices of the non-minimal coupling function F (ψ) [30][31][32][33][34][35][36]. The first example was provided in [30,31] assuming a linear coupling (F (ψ) ∝ ψ).…”
Section: Introductionmentioning
confidence: 99%